Indicators for proper management of surgical drains following pancreaticoduodenectomy. Issue 7 (14th January 2014) - Uemura, Kenichiro; Murakami, Yoshiaki; Sudo, Takeshi; Hashimoto, Yasushi; Kondo, Naru; Nakagawa, Naoya; Sasaki, Hayato; Ohge, Hiroki; Sueda, Taijiro
Abstract Background The indicators for proper drain management following pancreaticoduodenectomy (PD) remain unclear. Our aim was to identify appropriate timing and proper indicators for safe drain management after PD. Methods Prospectively collected data from 200 patients who underwent PD were evaluated. Postoperative clinical factors for clinically relevant pancreatic fistulas (CR‐POPFs) and management of surgically placed drains were analyzed retrospectively. Results CR‐POPFs occurred in 8% of patients. By logistic regression analysis, one factor (non‐serous fluid in the drain) on postoperative day (POD) 1 and two factors (non‐serous fluid in the drain and serum CRP levels) on POD 3 and 4 were significantly associated with CR‐POPFs. Receiver operating characteristic analysis demonstrated that combined predictive factors on POD 4 were the most accurate. Of 163 patients with serous fluid in the drain and CRP <15.6 mg/dl on POD 4, 1% had CR‐POPFs, but no patient required POPF‐related re‐drainage. In contrast, among 37 patients with non‐serous fluid in the drain or CRP levels ≥15.6 mg/dl, 35% had CR‐POPFs, and 8% required POPF‐related re‐drainage. Conclusions A combination of CRP levels and the color of surgical drain fluid, not POD1 or 3, but on POD 4, may be the most accurate indicators for safe drain management following PD. J. Surg. Oncol 2014; 109:702–707. © 2014 Wiley Periodicals, Inc.